Into the wild : wilderness photography in Tasmania. - Haygarth, Nic; Malor, Deborah S. (Deborah Sue); Quilliam, Damien; Addison, Jon.; Queen Victoria Museum and Art Gallery (Launceston, Tas.) (Launceston, Tas. : Queen Victoria Museum & Art Gallery, 2013)
"Compiling a fascinating body of landscape photography, Into the Wild documents the development of wilderness photography in Tasmania from its earliest days to the present, and charts shifting attitudes to the natural world. Drawing on the collection of the Queen Victoria Museum and Art Gallery, Tasmanian Archive and Heritage Office, and private collections, this is an unforgettable journey into the wild."--Back cover.
Curated by Damien Quilliam and Jon Addison ; texts by Nic Haygarth and Deb Malor.
Catalogue of an exhibition held at the Queen Victoria Museum & Art Gallery, Launceston, Tasmania, 15 March 2013 - 15 February 2014.
Includes bibliographical references.
Keywords: Landscape photography -- Tasmania -- Exhibitions; Landscape photography -- Tasmania -- History; Wilderness areas -- Tasmania -- Pictorial works; Photographers -- Tasmania -- History; Landscape photography -- Tasmania -- Exhibitions; Wilderness areas -- Tasmania -- Pictorial works; Australian